Fracture behavior of adhesively bonded carbon fabric composite plates with nano materials filled polymer matrix under DCB, ENF and SLS tests. (15th October 2018) - Srivastava, Vijay K.; Gries, Thomas; Quadflieg, Till; Mohr, Benjamin; Kolloch, Martin; Kumar, Parshant
Highlights: Interlaminar fracture toughness of adhesively bonded joint is higher in mode I than mode II. Mode I toughness value of GnPs-epoxy bonded joint is better than CBs-epoxy and pure-epoxy bonded joint. The resistance to crack growth is improved due to inclusion of fillers in DCB and ENF adhesive bonded joints. Abstract: In our earlier paper [Srivastava et al. Eng. Fract Mech, 180 (2017)] we found that mode I, mode II fracture toughness of carbon nanotubes (CNTs) filled woven carbon fabric composites increases with the addition of nanofillers. In order to prove the effect of nanofillers on adhesively bonded joints of woven carbon fabric laminates, the present study is conducted under double cantilever beam (DCB), end notched flexural (ENF) and single lap shear (SLS) tests. Graphene nanoplates (GnPs) filled epoxy resin, and carbon blacks (CBs) filled epoxy resin, and pure epoxy resin adhesives were used to prepare the DCB, ENF and single lap adhesively bonded joint specimen from two similar woven carbon fabric composite plates to measure them. Fracture toughness (mode I mode II) and shear strength of adhesively bonded joints were determined. The results show that the adhesively bonded woven carbon fabric composite joints with GnPs-filled epoxy resin and CBs-filled epoxy resin adhesives give better fracture toughness mode I, mode II and shear strength compare to pure epoxy resin adhesively bonded composite specimen. Mode I value is lower than mode II value due to the sharp propagation of cracks under tensile stress. Scanning electron microscopy (SEM) was utilized to monitor the distribution of nanofillers within the adhesively bonded texture to examine the effect of fracture surfaces in the bonded DCB, ENF and single lap shear joint specimens respectively.